Penerapan problem based learning dengan pembelajaran berdiferensiasi terhadap kemampuan pemecahan masalah di SD - Anggraini, agmelia Fatika; Profithasari, Nindy; Azizah, Alif Luthvi; Erni, Erni (Universitas Sebelas Maret, 2026)
The problem addressed in this study is the low level of problem-solving ability in the subject of Natural and Social Sciences (IPAS) among fourth-grade students at SD Aisyiyah. This study aims to examine the effect of the Problem-Based Learning (PBL) model integrated with differentiated instruction on students’ IPAS problem-solving abilities. A quasi-experimental method was employed using a non-equivalent control group design. The population of this study consisted of all fourth-grade students at SD Aisyiyah. The sampling technique used was saturated sampling, involving a total of 37 students. Hypothesis testing was conducted using simple linear regression analysis. The results indicated that Fcount > Ftable, demonstrating a significant effect of implementing the Problem-Based Learning model combined with differentiated instruction on students’ problem-solving abilities in IPAS. Therefore, it can be concluded that the integration of Problem-Based Learning and differentiated instruction positively influences the IPAS problem-solving abilities of fourth-grade elementary school students at SD Aisyiyah in the 2025/2026 academic year.